Handbook on managerial selection techniques - Md. Som, Hishamuddin (Penerbit UTM, 2000)
This books presents critical selection techniques that are employed by companies in choosing the right managers. Typical techniques such as application forms, curriculum vitae (CV), interviews, psychological (cognition and personality) tests are described and the validity of each technique is discussed and substantiated by research evidences. This handbook also offers useful tips from the practitioners´ perspectives in the process of filtering unsuitable candidates and choosing the most qualified ones. This book is suitable as a supplementary reference for students as well as researchers in Human Resource Management and for practitioners who have been interests in developing their skills in selection techniques.